2021
DOI: 10.1155/2021/6631921
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Adjuvant Intravitreal Treatment with Autologous Bone Marrow-Derived Lineage-Negative Cells in Retinitis Pigmentosa

Abstract: Background. Autologous bone marrow-derived lineage-negative (Lin−) cells present antiapoptotic and neuroprotective activity. The aim of the study was to evaluate the safety and efficacy of novel autologous Lin− cell therapy during a 12-month follow-up period. Methods. Intravitreal injection of Lin− cells in 30 eyes with retinitis pigmentosa (RP) was performed. The fellow eyes (FEs) were considered control eyes. Functional and morphological eye examinations were performed before and 1, 3, 6, 9, and 12 months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In parallel, intravenous administration of UC-MSCs indicated acceptable results with the successful efficiency of around 90% [ 473 , 474 ]. The similar results have been also achieved by BM-MSCs [ 475 477 ]. Sub-tenon injection of placenta-derived mesenchymal stem cells (PD-MSC) rescued the RGCs and improved the visual acuity [ 478 ].…”
Section: Current Approaches Of Photoreceptor Regenerationsupporting
confidence: 84%
“…In parallel, intravenous administration of UC-MSCs indicated acceptable results with the successful efficiency of around 90% [ 473 , 474 ]. The similar results have been also achieved by BM-MSCs [ 475 477 ]. Sub-tenon injection of placenta-derived mesenchymal stem cells (PD-MSC) rescued the RGCs and improved the visual acuity [ 478 ].…”
Section: Current Approaches Of Photoreceptor Regenerationsupporting
confidence: 84%
“…Recently, Wiącek et al reported intravitreal transplantation of autologous bone marrow-derived lineage-negative (BM lin − ) cells in RP patients with the disease incidence ranging from few years to more than 10 years. 49 A significant improvement in the BCVA and BCDVA (best-corrected distance visual acuity) was reported by the patients at the 12-months follow-up period, and improvement in the visual parameters was more pronounced in patients who had symptoms for less than 10 years and maintained functional foveal cones. The study also reported retinal detachment in three cases, with two cases requiring surgery to achieve complete retinal attachment.…”
Section: Clinical Trials With Stem Cellsmentioning
confidence: 78%
“…The study also reported retinal detachment in three cases, with two cases requiring surgery to achieve complete retinal attachment. 49 In two separate clinical trials, Limoli et al transplanted autologous adipose-derived stem cells (ADSCs) from the stromal vascular fraction of the adipose tissue along with platelets obtained from platelet-rich plasma and adipose stromal cells of the orbital fat in the subscleral space. The study reported an improvement in visual performance with no adverse effects.…”
Section: Clinical Trials With Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Weiss and Levy, authors administrated autologous bone-marrow stem cells to 33 eyes of 17 patients through retrobulbar, subtenons, intravitreal or intravenous injections, observing an improvement of 7.9 Snellen lines in 15 eyes [64]. Wiącek et al performed intravitreal injections of autologous bone marrow stem cells in RP patients with a disease story of a few years or more than 10 years, which resulted in a significative improvement in BCVA and best-corrected distance visual acuity (BCDVA) in a 12 months follow-up [65]. In a non-randomized phase I clinical trial involving 14 patients with RP, an intravitreal injection of bone marrow MSCs was performed, aiming to compare the BCVA at 1 and 7 years from the therapy.…”
Section: Use Of Mscs In Retinitis Pigmentosamentioning
confidence: 99%